Resource-sharing cognitive radio networks in commercial and military environments - Ian Bajaj (2017)
Cognitive radio (CR) provides the platform for dynamic spectrum sensing, spectrum allocation and intuitive decision making in a very rigid spectrum framework architecture. Accessing white spaces in licensed spectrum through spectrum hopping and managing interference in free-to-use spectrum are means by which CR can help improve the overall spectrum efficiency. But utilizing these spectrum resources generally comes at a price, whether that be a monetary cost or interference to transmission. Resource-sharing therefore demands a two-way exchange for users to e ffectively transmit simultaneously across any spectrum. We investigate how this cost changes given the application of CRs in a commercial or military setting.